Military Loyalty as a Moral Emotion. Issue 3 (July 2021) - Connor, James; Andrews, Dia Jade; Noack-Lundberg, Kyja; Wadham, Ben
Loyalty between soldiers is idealized as an emotion that promotes cohesion and combat effectiveness. However, little empirical work has examined how military personnel understand, feel, and enact loyalty. We use a symbolic interactionalist informed frame to explore the lived experience of 24 retired Australian Defence Force members via in-depth semi-structured interviews. Our analysis revealed three core themes: (1) Loyalty as reciprocity, where there was an expectation that loyalty would be returned no matter what. (2) The importance of emotional connection for cohesion. (3) Loyalty as a prioritizing process, where a soldier's loyalties gave them a way of choosing between competing demands. Loyalty is a moral emotion that enabled sensemaking. Close interpersonal loyalties tended to trump wider/diffused loyalties. Respondents understood their loyalties to fellow soldiers within wider social constructs of mateship and professionalism. The findings show the risks that come from a reliance on loyalty for combat cohesion.